IDENTIFYING VISITOR PREFERENCES FOR LOCATIONS AND FEATURES IN BOGOR BOTANICAL GARDEN, INDONESIA, USING GPS TRACKING AND GEOTAGGED PHOTOS - Akhmad Arifin Hadi; Yusuke Mizuuchi; Dwi Setyanti; Tsuyoshi Honjo; Katsunori Furuya (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2017)
Research on visitors’ landscape preferences in a botanical garden is useful for understanding what visitors see while they visit the site. Analyzing visitors’ preference by using GPS tracking data and Visitors’-Employed Photography (VEP) is one of approach that successfully implemented in some studies. GPS loggers and visitors’ photos were used in this study to identify and locate features considered impressive by visitors. This research involved 35 normal visitors of Bogor Botanical Garden (BBG) as respondents, who were asked to capture impressive landscape features while visiting the BBG. Each respondent used their own smartphone or camera to take photographs and recorded their actual positions using a GPS logger. The data of GPS tracking and geo-tagged photos were exported into ArcGIS. The 20 by 20 meters square cell were joined with points' data to calculate density of tracking points and photos points. A cell was categorized as hotspots if the number of points more than 2.5 times of standard deviation. The results show that respondents were concentrated on several geographic locations within the BBG; the most-photographed features were water, structures, and plants. Interestingly, the most-photographed plants were those arranged for recreational (rather than botanical or educational) purposes, suggesting new considerations for managers of botanical gardens.